Identification of different serotypes of Foot and Mouth Disease Virus from Sylhet district, Bangladesh; by adoption and application of RT-PCR and mRT-PCR. - Kadir, A; Ahmed, S (International Journal of Natural Sciences, 2016)
Foot and mouth disease (FMD) is a major constraint for livestock in Bangladesh; as outbreak of FMD remains uncontrolled despite vaccination. Accurate and Rapid detection of FMD virus with its serotype in field samples is indispensible. So, molecular detection of FMDV was adopted using RT-PCR (reverse transcription- polymerase chain reaction) and mRT-PCR (multiplex reverse transcription-polymerase chain reaction). Ten (10) FMD suspected clinical samples from cattle of two different outbreak areas of Sylhet district of Bangladesh was collected. One set of universal primer (P32:P33) was used in RT-PCR for the detection of FMD virus regardless of their serotypes and a cocktail of primer mix (P38:P40:P74-77:P110) was used in mRT-PCR intending the identification of the serotypes A, O, C and Asia 1. Using universal primer sets 90% of the samples generated amplicon of expected size, indicating the samples containing FMD virus. By mRT-PCR, two serotypes, O and Asia 1 were successfully, whereas type C and A were absent in this study. Out of the 9 viruses; 7 was identified as serotype O and 2 were identified as Asia-1. Our study indicates that FMDV serotype O and Asia-1 was circulating in the two upazilas (Sub-district) of Sylhet district during the study period. Our study also endorses that, RT-PCR and mRT-PCR can successfully be used for a dependable and rapid detection of FMD. However, presence and detection of O and Asia-1 serotype of FMDV through this study and serotype A by other researchers emphasizes the critical need for use of trivalent vaccine in the field. International Journal of Natural Sciences (2014), 4(1) 28-34